Solid Catalyst in Esterification and Transesterification Reactions for Biodiesel Production: A Review - Simpen, Nengah; Winaya, IN. Suprapta; Subagia, ID.G. Ary; Suyasa, IW. Budiarsa (International Journal of Engineering and Emerging Technology; Vol 5 No 2 (2020): July - DecemberDO - 10.24843/IJEET.2020.v05.i02.p29, 2020)
Biodiesel is considered as an important substitute for the replacement of fossil diesel due to its biodegradable, renewable and non-toxicity to environment. Biodiesel consist of mixture of mono alkyl esters of long chain fatty acids. It is produced from vegetable oils, animal fats and waste cooking oil. Solid catalysts are promising and advantageous for biodiesel production because those could be reusable, environmentally benign and are more effective than liquid catalysts. Moreover, the application of solid catalysts does not produce soaps through triglycerides saponification or free fatty acids neutralization. When triglycerides as major component of oil react with alcohol (methanol or ethanol) to form biodiesel in the presence of base catalyst, this called is transesterification. When acid catalysts are used for reducing free fatty acids to form biodiesel, this called is esterification. The application of solid catalysts in esterification and transesterification reactions for biodiesel production are discussed in this review.